Pharmacological priming of adipose‐derived stem cells for paracrine VEGF production with deferoxamine. (30th July 2013) - Liu, Guei‐Sheung; Peshavariya, Hitesh M.; Higuchi, Masayoshi; Chan, Elsa C.; Dusting, Gregory J.; Jiang, Fan
Abstract: Adipose‐derived stem cells (ASCs) show great potentials in applications such as therapeutic angiogenesis, regenerative medicine and tissue engineering. Pharmacological preconditioning of stem cells to boost the release of cytoprotective factors may represent an effective way to enhance their therapeutic efficacy. In this study, the aim was to determine whether deferoxamine can enhance the release of vascular endothelial growth factor (VEGF) from in vitro expanded ASCs. It is demonstrated that deferoxamine (50–300 μm ) upregulated VEGF expression in a concentration‐ and time‐dependent fashion. At the concentrations used, deferoxamine did not show any cytotoxic effects. The stimulatory effect of deferoxamine on VEGF expression was mediated by augmentation of hypoxia inducible factor‐1 in ASCs, but independent of its antioxidant properties. Moreover, deferoxamine enhanced the paracrine effects of ASCs in promoting the regenerative functions of endothelial cells (migration and in vitro wound healing activities). This study provides evidence that deferoxamine might be a useful drug with low cell toxicity for pharmacological preconditioning of ASCs to enhance their capacity of VEGF production. Copyright © 2013 John Wiley & Sons, Ltd.